EXCHANGE RATE DYNAMICS AND THE BALANCE OF PAYMENTS IN SIERRA LEONE (2014)
There is a strong relationship between exchange rate movements and the Balance of Payments (BoP). In Sierra Leone, exchange rate depreciated steadily from 1.05 Leone (Le) to 1.00 United States dollar (US$) in 1980 through Le151.45/US$1 in 1990, Le2,092/US$1 in 2000 to Le3,978.09/US$1 in 2010. In the same periods, the BoP as a percentage of gross domestic product fluctuated between -15.0% and 3.0%. The literature has focused mainly on the effects of exchange rate on inflation, revenue and economic growth, while its effects on the BoP are hardly examined. This study investigated the impact of exchange rate dynamics on the BoP in Sierra Leone covering the period between 1975 and 2010. A structural macroeconomic model, derived from the elasticity, absorption and monetary theoretical frameworks to BoP determination, was estimated. The model was disaggregated into Current Account Balance (CAB), Financial Account Balance (FAB), Capital Account Balance (KAB) and the consumer price index. An Autoregressive Distributed Lag bounds testing technique was used to determine the dynamic (the short-run and long-run measured by elasticities) effects of exchange rate on the key variables. These elasticities were used to determine the time path of the changes in the CAB and BoP, as postulated by the J-curve phenomenon and the Marshall-Lerner condition (sum of exports and imports demand elasticities be greater than one for depreciation to improve the CAB and BoP). The data used for the estimations were collected from the International Financial Statistics of the International Monetary Fund. The problems of serial correlation and endogeneity were addressed using the Akaike and Schwarz criteria. The Cumulative Sum (CUSUM) and CUSUM squares of the recursive residuals were used to determine the stability and reliability of the parameter estimates. A depreciation of the exchange rate had both short-run and long-run dynamic effects on the BoP. In the short-run, a 10.0% depreciation of the exchange rate deteriorated the overall BoP deficit by 4.6%, and improved it by 3.4% in the long-run. The effects of exchange rate on the components of BoP differed substantially as the total demand elasticity for both exports and imports was 0.3 in the short-run and 1.2 in the long-run. This suggested that the depreciation initially led to a deterioration of the CAB deficit (due to time lags in executing trade contracts and delivery of goods) and then gradually improved thereafter. The effects on the FAB (0.03%) and KAB (0.01%) were negligible in the short-run, but improved to 0.7% and 0.5%, respectively in the long-run. The results confirmed the existence of the J-curve phenomenon and the Marshall-Lerner condition only in the CAB and the overall BoP positions. The effect on BoP of exchange rate pass-through to domestic price was 80.0%. Exchange rate movements significantly influenced the current account balance and the balance of payments, both in the short-run and long-run, while it only affected the financial and capital account balances moderately in the long-run. Accordingly, exchange rate policy is important for the restoration of balance of payments equilibrium by the monetary authority